فريق جبهة التحرير الوطني لكرة القدم سفير القضية الجزائرية (1958- 1962 - كلة نصيرة (University of Eloued جامعة الوادي, 2024)
تهدف هذه الورقة البحثية الى تسليط الضوء على فريق كرة القدم لجبهة التحرير الوطني من خلال ابراز دوره الدبلوماسي في دعم الثورة التحريرية، والدعاية الإعلامية عبر المحافل الدولية من خلال جولاته عبر العالم رافعا الراية الوطنية مناديا بالقضية الجزائرية، أيضا الدعم والإعانات المادية التي ساهم بها لصالح خزينة الثورة من اجل مواصلة مسيرتها النضالية. نقول في الأخير لعب فريق جبهة التحرير الوطني دورا مهما في دعم و مساندة الثورة التحريرية، فكان خير سفير للقضية الوطنية، لقد شكل دعاية مجانية للثورة الجزائرية عبر المحافل الدولية، حيث ساهم في كسب التأييد الدبلوماسي و الدعم المادي لها مما عجل في نيل الاستقلال. This research paper aims to shed light on the football team of the National Liberation Front by highlighting its diplomatic role in supporting the liberation revolution, and media propaganda through international forums through its tours around the world, raising the national flag and calling for the Algerian cause, as well as the financial support and subsidies that it contributed for the benefit of the treasury revolution in order to continue its struggle. Finally, we say that the National Liberation Front team played an important role in supporting the liberation revolution, and it was the best ambassador for the national cause, it constituted free propaganda for the Algerian revolution through international forums, as it contributed to gaining diplomatic support and material support for it, which accelerated the achievement of independence.
Keywords: الرياضة; كرة القدم; جبهة التحرير ال; طني; القضية الجزائرية; Sports; soccer; National Liberation Front; diplomacy; Algerian case